Video Surveillance: Practices and Policies in Europe - Webster, C. William R (IOS Press, 2014)
Video surveillance cameras and systems, commonly referred to as Closed-Circuit Television (CCTV) despite their increasingly networked character, are a defining feature of modern society. Their widespread use, as fixed or mobile devices, deployed for a range of purposes and by a variety of public and private actors, is now unsurprising and generally accepted in most countries. The normality of these surveillance practices, and the technologies used, are a world away from the early tube cameras used for local broadcasting and the isolated monitoring of industrial processing in the 1930s and 1940s. The diffusion processes, which have led to the exponential growth of these cameras and systems, have included evolutions in the design, function and capabilities of systems, especially around opportunities for extended, combined and automated systems offered by new information and communication technologies.